Prenatal health-related quality of life assessment among Hungarian pregnant women using PROMIS-43 - Vahideh MoghaddamHosseini; Monika Gyuró; Alexandra Makai; Katalin Varga; Masoumeh Hashemian; Ákos Várnagy (Elsevier, 2021)
Background: Assessing prenatal health-related quality of life (HRQoL) by parity using a comprehensive consistent instrument with the transient nature of pregnancy is still under investigation. Objective: To assess HRQoL and specify its predictors among expectant women in Hungary through Patient Reported Outcomes Measurement Information System (PROMIS-43). Method: s: 477 healthy pregnant women were asked to fill the Hungarian version of PROMIS-43 and further instruments in late pregnancy.The PROMIS-43 investigates seven parameters, including anxiety, ability to participate in social roles and activities, depression, fatigue, sleep disturbance, physical function, and pain interference. Results: While physical function and fatigue subscales obtained the highest proportion in the mild and moderate range, respectively, other subscales were felled into the normal range in all participants. A comparison of parity showed that the mean T-score of subscale "Anxiety" was significantly higher in nulliparous than that of in multiparous women (p = 0.02). The assessments indicated that the predictors, including parity, anxiety, and depression were the most common predictors for the poor HRQoL domains in both the nulliparous and multiparous women. In nulliparous, social support was a significant predictor for better HRQoL in depression, fatigue, and pain intensity domains. In multiparous, the strongest predictors included social support for lower depression, wanted pregnancy for lower pain intensity, and previous emergency cesarean section for higher pain intensity subscale. Conclusion: The results of PROMIS-43 support the fact that the screening and continuous assessment of physical function and psychological status at early and over pregnancy is still on demand to optimize the outcomes of maternity care.